Evaluation of Formative Research in Online and Distance Higher Education in Latin America and the Caribbean - Morocho Quezada , Mary (2023)
Research training is fundamental to the quality of higher education. It is from this conception that formative research is inherent in the curricula of professional training in the various areas of knowledge, thus contributing to the purposes of the teaching activity, and offering the student the possibility of acquiring a set of research skills and competencies, aimed at promoting the development of theoretical knowledge in the exercise of academic activity. Formative research, being a non-improvised process, must also be very clear about the standards that allow demonstrating that students have effectively developed knowledge and research skills; in this way, the evaluation systems in the region consider within their structure a set of aspects to be evaluated that allow evidencing the development of formative research in higher education institutions. This scientific editorial systematically analyzes the models of evaluation of distance and online education at the regional level, developed and put into practice by evaluation and accreditation agencies, and based on this set of dimensions, characteristics, factors, standards, and indicators, determine through a comparative analysis how the evaluation of formative research in distance higher education in Latin America and the Caribbean is carried out.